Preliminary Review On Preparations In Malaysia To Improve Stem Education - Chong, Chee Jiun (UMT Publisher, 2019)
Strengthening the knowledge of Science, Technology, Engineering, and Mathematics (STEM) in human populations is one of the key elements in the fourth sustainable development goals (SDG4). Many countries are facing challenges to implement STEM education. Findings from international benchmarking such as Trends in International Mathematics and Science Study (TIMMS) and Programme for International Student Assessment (PISA) revealed that students who originate from East Asia countries outperformed students from other countries consistently. This implies that the educators in East Asia countries are employing good strategies in the implementation of STEM education. This paper reviews the preparation of Malaysians in implementing STEM education and compares them with the preparations made by these East Asia countries. This is significant because it would help to benchmark Malaysians’ effort in achieving SDG4. From this study, it was found that Malaysia has established necessary interventions suggested by the theory of change, but its effectiveness is yet to be known. The study allows educational researcher to identify the research opportunity related to educational research related to STEM education in Malaysia.